Selective ATP-Binding Cassette Subfamily C Gene Expression and Proinflammatory Mediators Released by BEAS-2B after PM2.5, Budesonide, and Cotreated Exposures - Jarline Encarnación-Medina; Rosa I. Rodríguez-Cotto; Joseph Bloom-Oquendo; Mario G. Ortiz-Martínez; Jorge Duconge; Braulio Jiménez-Vélez (Mediators of Inflammation)
ATP-binding cassette subfamily C (ABCC) genes code for phase III metabolism proteins that translocate xenobiotic (e.g., particulate matter 2.5 (PM2.5)) and drug metabolites outside the cells. IL-6 secretion is related with the activation of the ABCC transporters. This study assesses ABCC1–4 gene expression changes and proinflammatory cytokine (IL-6, IL-8) release in human bronchial epithelial cells (BEAS-2B) exposed to PM2.5 organic extract, budesonide (BUD, used to control inflammation in asthmatic patients), and a cotreatment (Co-T: PM2.5 and BUD). A real-time PCR assay shows that ABCC1 was upregulated in BEAS-2B exposed after 6 and 7 hr to PM2.5 extract or BUD but downregulated after 6 hr of the Co-T. ABCC3 was downregulated after 6 hr of BUD and upregulated after 6 hr of the Co-T exposures. ABCC4 was upregulated after 5 hr of PM2.5 extract, BUD, and the Co-T exposures. The cytokine assay revealed an increase in IL-6 release by BEAS-2B exposed after 5 hr to PM2.5 extract, BUD, and the Co-T. At 7 hr, the Co-T decreases IL-6 release and IL-8 at 6 hr. In conclusion, the cotreatment showed an opposite effect on exposed BEAS-2B as compared with BUD. The results suggest an interference of the BUD therapeutic potential by PM2.5.